THE TRANSFORMATION OF THE MARINA BAY SAND AREA: THE HISTORY OF MANAGING THE ENERGY BALANCE OF SINGAPORE - Sikumbang, Idris Hadi; Yola, Lin (International Review of Humanities Studies, 2023)
As an island country, Singapore has limited territory so it needs appropriate policies to arrange the balance between its population and territory. After separated with the Federation of Malaya in 1965, Singapore drew up a regional plan involving UNDP. Urban Redevelopment Authority is the institution that plays a role in carrying out this policy. Singapore organizes its slum areas for the better, one of which is located at Marina Bay Sand and the current transformation is in line with the Sustainable Development Goals program to maintain the balance of urban energy needed by Singaporeans. This approach involves the private sector in regional development and planning which is always organized following developments in the global community. This research was conducted using a sociological historical change approach by observing changes in Singapore government policies in managing the environment in the Marina Bay Sands area as well as field observations using qualitative methods through taking field data to the Marina Bay Sands area in Singapore, as well as unobtrusive observation, namely collecting data from informants indirectly through the social media channel Youtube.